Meeting the information needs of ghanaian cocoa farmers: are farmer field schools the answer? (Journal of Science and Technology, 2016)
A number of farmer-led approaches to technology transfer have emerged in recent times to replace the largely discredited Transfer of Technology (TOT) and Training and Visit (T&V) models of agricultural extension. One such initiative is the Farmer Field School (FFS), an experiential learning approach originally developed in Southeast Asia for the integrated management of rice pests but adaptable to other crops and even to livestock and fisheries. The experiences in the use of FFS in other crops have beenapplied to cocoa in studies in the Central and Ashanti regions of Ghana. This study used a mixed method of group interviews, questionnaire survey and in-depth one-on-one interviews to elicit information from farmers in Atwima and Amansie-West districts of Ashanti where the sustainable tree crops programme (STCP) has been conducting FFSs since 2002, with the object of evaluating the extent to which the FFS approach could augment existing extension strategies in meeting farmers' information needs. The sample included participants and non-participants alike providing a basis for comparativeanalysis. The results indicate that majority of the farmers (70%) rely on their social networks of friends, neighbours and family members for information and advice with only 13% regarding extension agents as their main source of advice. No significant differences (P